Made in Japan 100 new products - Pollock, Naomi R; Sudo, Reiko (London Merrell, 2012)
A selection of outstanding Japanese products of this century, from gadgets and furnishings to office supplies and decorative objects. Features a comprehensive introduction to the history and traditions of Japanese product design and includes biographies of the leading designers, including Naoto Fukasawa, Tokujin Yoshioka and Toyo Ito
2
Keywords: Industrial design -- Japan -- History -- 21st century; Industrial design; New products -- Japan -- History -- 21st century; New products; Japan